Veggies for breakfast : 100 delicious plant-focused recipes for healthier mornings - Galloway, Willi (Sasquatch Books, 2025)
"Eat more veg, more often! These quick, easy, and tasty vegetarian-ish breakfast recipes offer tons of adaptable, mix-and-match, and make-ahead recipe ideas to take the stress out of your morning and start the day off right. Like Six Seasons but for breakfast, Veggies for Breakfast will win over even the most skeptical breakfast skipper and get the veg party started early in the day with easy, delicious, and seasonal savory and sweet breakfasts. Cooking up a breakfast beyond cereal, smoothies, and yogurt is often perceived as a time suck, especially during the week when you're frantically packing lunches for the family or trying to get out the door. But Willi Galloway is here to share her love letter to the vibrant world of vegetables, a road map for making delicious, healthful morning meals, and a call to reconsider what exactly constitutes breakfast. From classic avocado toasts to innovative ways to sneak green veg into sweet breakfasts, she makes mornings a breeze. Imagine veggies piled on toast, stuffed into tacos, heaped into bowls, stir-fried in skillets and baked with eggs-all with a broad set of flavors to help you break out of ruts. Willi guides you on a path to eating more vegetables more often by widening the definition of breakfast and diversifying what you eat. Recipes include: Cacio e Pepe Oatmeal Summery Strawberry Toast with Chèvre, Cucumber, and Avocado Shakshuka with Seared Halloumi Carrot Cake Overnight Oats with Pepita Crunch Tater Tot Breakfast Burritos"--